A New Relationship between Ownership–Control Wedge and Overinvestment Practices: Evidence from Korean Business Groups (Chaebol). (April 2016) - Goh, Jaimin; Lee, Jaehong; Cho, Jungeun
Abstract: This study examines the effects of controlling shareholders' ownership–control wedge on firms' overinvestment practices. In addition, it further investigates the incentive effects of controlling shareholders' cash flow rights on firms' overinvestment. We find a non‐monotonic relation between controlling shareholders' ownership–control wedge and a firm's overinvestment. Specifically, the relation between controlling shareholders' wedge and overinvestment is significant for certain wedge levels. Thus we conclude that controlling shareholders with certain levels of wedge expropriate minority shareholders' benefits since the marginal benefit exceeds the marginal cost. We also document that cash flow rights are effective to reduce a firm's overinvestment to certain levels.